Biologic therapy in the management of asthma. Issue 4 (August 2016) - McCracken, Jennifer L.; Tripple, Julia W.; Calhoun, William J.
Abstract : Purpose of review: Current asthma management relies on inhaled corticosteroids, but some asthma is not well controlled with inhaled steroids alone or in combination with long-acting bronchodilators or leukotriene pathway inhibitors. The field of biologic therapy has grown dramatically in the past two decades, with current availability of three molecules, with two distinct and highly selective approaches to interfering with the allergic and eosinophilic airway inflammation common to most asthma. This review summarizes current and future options for incorporating biologic therapy into the overall management of asthma. Recent findings: Two new biologic agents have been recently introduced in the United States market, supported by well controlled, randomized clinical trials. These trials have provided insight into the types of patients who are most likely to benefit from these novel agents. Summary: In asthma patients with frequent exacerbations, the addition of a biologic agent targeting the interleukin-5 pathway, or immunoglobulin E, can significantly reduce exacerbations and improve asthma control. The clinical predictors of utility of specific agents overlap with one another, highlighting the importance of clinical judgment in the overall management of this complex disorder.